A wind-turbine for autonomous stations for radio detection of neutrinos - Nelles, Anna (Proceedings of Science, 2019)
A future large radio array for the detection of neutrinos may need to be built in remote areas without access to a power grid, such as the Antarctic ice-shelf or Greenland. In such a scenario lifetime will need to be optimized by combining different renewable and autonomous power sources. The ARIANNA experiment on the Ross-Ice-Shelf has run stably on solar power during the Austral summer, as soon as the Sun was more than 3 degrees above the horizon. However, the dark months of polar winter provide essential lifetime, especially with respect to multi-messenger studies. We will present a wind-turbine that has been custom-designed for the ARIANNA experiment to be radio-quiet, sensitive to low winds and able to sustain extreme Antarctic weather. The first important milestone was achieved in 2018 when a first wind turbine survived the winter months and powered a station for 24% of the winter time. We will report on the in-situ performance of the second-generation turbine already reaching 39% uptime during the weak summer winds and the perspective of this technique.
CRIS-Team Scopus Importer:2021-04-20